Забезпечення стабільності кольору світлодіодів протягом терміну використання - Лашко, Е. І. (ХНУРЕ, 2024)
Analyzing the methods of ensuring the color stability of LEDs during their service life is an important topic, since LEDs are used in most indicators, such as displays, various indicating devices and LED lamps, replacing outdated incandescent lamps and other analogues. With time their color changes, resulting in incorrect color rendering. A change in the color of the light can also lead to a decrease in energy efficiency due to defects in the structure of the diode or its degradation. The work aims to identify the main factors leading to changes in the emission spectrum of modern light-emitting diodes, to study ways to solve the problem of LED degradation, to analyze existing methods for increasing the service life of such devices and to select the most optimal ones.
Keywords: світлодіод; стабільність кольору світлодіодів